Erythrocyte oxidative damage and antioxidant mechanisms in Veterinary Medicine - Machado, Luciana Pereira; Kohayagawa, Aguemi; Saito, Mere Erika; Silveira, Veridiana Fernandes da; Yonezawa, Letícia Andreza (Revista de Ciências Agroveterinárias, 2009)
Free radicals are produced continuously in normal cell metabolism and in various pathological events. When in excess, they may cause oxidation of biologic molecules. As a protection mechanism, the body has a complex system of antioxidant defense. The imbalance between oxidative challenge and antioxidant defense capacity is called oxidative stress. Erythrocytes play vital functions in the body which can be compromised due to oxidative stress. Red blood cells become vulnerable to oxidative injury due to their constitution. Membrane unsaturated lipids are highly susceptible to oxidation, and the presence of oxygen and iron enhances free radicals formation. Furthermore, red blood cells are unable to synthesize new lipids and proteins to replace those that have been oxidized. Therefore, the maintenance of antioxidant mechanisms, such as vitamins E and C, and enzymes superoxide dismutase, catalase, glutathione system, and metahemoglobin reductase is important to prevent and repair damages. This paper reviews information about the mechanisms of erythrocyte oxidative damage and antioxidant defense system, aiming to help veterinary professionals in diagnosis and treatment of erythrocyte oxidative stress related diseases.